دور المراجعة الداخلية في تفعيل الحوكمة في القطاع المصرفي دراسة ميدانية في المصرف التجاري السوري باللاذقية - زيود لطيف; علي حسين; نصور ريم محمد (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى دراسة دور المراجعة الداخلية في تفعيل الحوكمة في المصرف التجاري السوري باللاذقية. ولتحقيق أهداف البحث تمّ تصميم استبانة وتوزيعها على (43) إدارياً من العاملين بالمصرف. تمّ استخدام المنهج الوصفي التحليلي باستخدام الأدوات اللازمة لجمع الأدلة والبيانات. وبعد الدراسة والتحليل تمّ التوصل إلى النتائج الآتية: 1- إن تطبيق نظام محكم لأعمال المراجعة الداخلية، يؤدي إلى تفعيل الحوكمة في المصرف التجاري السوري باللاذقية. 2- إن القيام بعملية المراجعة الداخلية وفق المعايير المهنية الواجبة، يؤدي إلى تفعيل الحوكمة في المصرف التجاري السوري باللاذقية. 3- إن استقلالية إدارات المراجعة الداخلية يؤدي إلى تفعيل الحوكمة في المصرف التجاري السوري باللاذقية. 4- إن متابعة وتقييم نظم وإجراءات إدارة المخاطر، تؤدي إلى تفعيل الحوكمة في المصرف التجاري السوري باللاذقية. The research aims to study the role of internal audit in the activation of governance in the Commercial Bank of Syria Latakia. To achieve the objectives of the research a questionnaire was designed and distributed to (43) managers of the bank Staff. The researcher used the descriptive method and analytical method using the tools necessary for the collection of evidence and data. After study and analysis was reached the following conclusions: 1- The application of an elaborate system of internal audit leads to the activation of governance in the Commercial Bank of Syria Latakia. 2- Making internal audit in accordance with professional standards of due diligence leads to the activation of governance in the Commercial Bank of Syria Latakia. 3- The independence of the internal audit departments leads to the activation of governance in the Commercial Bank of Syria Latakia. 4- The monitoring and evaluation systems and risk management procedures lead to the activation of governance in the Commercial Bank of Syria Latakia.